The Use of Indonesian Children's Songs to Improve The Language Ability of Foreign Students at Suksa Muslim School - Zahra Tama Ritonga; Mutia Febriyana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to improve the Indonesian language skills of foreign students in class Matthayom 4 at Suksa Muslim School through the use of the Indonesian children's song "Balonku" as a learning medium. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, each including the planning stage, action implementation, observation, and reflection. The research subjects were 20 Thai students who are studying Indonesian at the elementary level. Data collection techniques were carried out through tests, observations, and documentation. The results of the study indicate that the use of Indonesian children's songs can significantly improve students' language skills, both in the aspects of Vocabulary Mastery, Pronunciation, Writing Accuracy. The improvement is seen from the average scores of students in the pre-action stage, cycle I, to cycle II. In addition, student learning activities have increased in terms of activeness, motivation, and emotional involvement during the learning process. Thus, Indonesian children's songs are proven to be effective in improving the language skills of foreign students.